Serum Level of Vascular Endothelial Growth Factor (VEGF) can be used to Assess Response of Radiation Therapy in Cervical Cancer - Ferry Armanza; Andrijono Andrijono; Bambang Sutrisna (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To compare the sensitivity and specificity of Squamous Cell Carcinoma (SCC) and Vascular Endothelial Growth Factor (VEGF) levels to assess the response of radiation therapy. Method: The study was conducted by the method of analytic observational cohort study in 24 patients with cervical cancer stage II-B and III-B in RSCM that met inclusion criteria. Examination of VEGF and SCC in serum samples was performed in the Prodia Laboratory Jakarta. The examination was conducted twice before and after radiation therapy. The subjects were treated by radiation therapy/chemoradiation according to standard procedures. After the completion of radiation was declared, the response of radiation therapy was conducted by clinical assessment. Result: Of the 24 subjects, we obtained a mean level of SCC pre-radiation was 23.43 ± 5.84 ng/ml and post-radiation was 2.19 ± 0.68 ng/ml. The mean VEGF pre-radiation was 790.41 ± 111.06 pg/ml and post-radiation was 497.47 ± 79.26 pg/ml. ROC curves of each tumor marker obtained SCC pre-radiation AUC 40%, p 0.53 (CI 0.18-0.68) and SCC post-radiation AUC 48.1%, p 0.91 (CI 0.21-0,75) can not be used as a diagnostic and prognostic factors of response to radiation therapy. VEGF pre-radiation produced an AUC of 17.5%, p 0.04 (CI 0.00-0.36), thus cannot be used as a prognostic factor for response to radiation therapy. VEGF after radiation produced an AUC of 92.5%, p 0.01 (CI 0.81-1.00), thus can be a diagnostic factor for response to radiation therapy. VEGF post-radiation with cut-off point 614.75 pg/ml had a sensitivity 80%, specificity 75%, NDP 94.12%, NDN 42.86%; RKP 3.2; RKN 0.26 and accuracy 79.16%. There is a significant correlation between the decrease of serum VEGF level post-radiation and a positive response of radiation therapy (p 0.01, CI 1.00-3.23). Conclusion: Examination of VEGF levels can be used to assess the response of radiation therapy with a sensitivity of 80% and specificity of 75%. Keywords: cervical cancer, SCC, therapeutic response, VEGF